Pengaruh Kenyamanan, Kesulitan, dan Persepsi Terhadap Penggunaan Bahasa Baku pada Mahasiswa Statistika Universitas Negeri Medan - Simamora, Tabita Paulina; Ingrid, Antonia; Simanullang, Junitro Andreas; Septianingtias, Indri Avisa; Damanik, Ayu Lestari; Dalimunthe, Syairal Fahmy (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Standard language is a variety of language that is accepted for use in official or formal situations. Standard language is the standard of communication used in the academic and professional world. Its use is important to ensure that the message conveyed is clear, formal, and in accordance with linguistic rules. However, in everyday life, students tend to use non-standard language more often in informal conversations, academic assignments, and discussions on campus. This study uses a quantitative approach with descriptive and inferential analysis methods to determine the effect of comfort, difficulty, and perception of the importance of standard language on the frequency of its use among Statistics students at Medan State University. Data were obtained by distributing questionnaires to 50 Statistics students selected using simple random sampling techniques. This study aims to analyze the frequency of use of standard language among Statistics students at UNIMED and to see the effect of comfort, difficulty, and perception on its use. The results of the analysis show that the majority of students use standard language in the categories